Health state utilities for chronic lymphocytic leukemia: importance of prolonging progression-free survival. Issue 5 (May 2015) - Kosmas, Charlotte E.; Shingler, Sarah L.; Samanta, Kunal; Wiesner, Christof; Moss, Paul A. H.; Becker, Ursula; Lloyd, Andrew J.
Abstract Chronic lymphocytic leukemia (CLL) is a largely incurable disease which affects patients' health related quality of life (HRQL). Treatment is often initiated when symptoms affect HRQL, and patients can experience many rounds of treatment throughout their life. Therefore, the economic burden of CLL can be high. Utility or preference weights for health states reflect the value of HRQL of a given health state and range from 1 (full health) to 0 (dead) and below (negative values possible). Nine health states were developed representing different CLL treatment lines or disease stages. One hundred members of the UK general public valued each health state using the time trade-off methodology. Progression-free survival (PFS) without therapy (mean utility = 0.82) was the least burdensome, with relapsed lines of treatment (mean utility = 0.42) representing the greatest burden. The results underline the value in maintaining a state of PFS for as long as possible.